(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The word printing or printmaking in India leads us to the history of printing through the mechanical movable type printing press in India, exactly 100 years after the invention of the printing press by the German technician John Guttenberg of Mainz, the printing trade was continued in various places by the French, Portuguese and Britishers in India, also printing in other mediums such as engraving, lithography and etchings have been introduced in India. This is found in extensive manner after the independence or the year 1950, where printmaking explored by the art students in the colleges, print studios and at other private individual studios. The important findings are regarding the exploration of various new printmaking mediums, the conceptualization of a print and use of other alternative materials and methods as to find new ways of expression using printmaking. In this paper I have tried to discuss different aspects and points that how it has spread out and came out as an important expressive creative tool for an artist to voice out using the medium.